2018
DOI: 10.1186/s12920-018-0374-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of NOS1 gene polymorphisms with cerebral palsy in a Han Chinese population: a case-control study

Abstract: BackgroundCerebral palsy (CP) is the leading cause of motor disability in children; however, its pathogenesis is unknown in most cases. Growing evidence suggests that Nitric oxide synthase 1 (NOS1) is involved in neural development and neurologic diseases. The purpose of this study was to determine whether genetic variants of NOS1 contribute to CP susceptibility in a Han Chinese population.MethodsA case-control study involving 652 CP patients and 636 healthy controls was conducted. Six SNPs in the NOS1 gene (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…However, many studies omitted the information needed to assess the reliability of ascertainment of CP, including age range at diagnosis and average age at recruitment, or as pertinent to the SCPE whether the child was ‘at least 4 years old when assessed’ 13 . Ten studies (18%) erroneously stated that they were compliant with the SCPE guidelines whereas the details on age at recruitment (Table S1) indicated that they were not, in the absence of any statement regarding confirmation of the diagnosis from the age of 4 years 21–30 . A third of studies ( n =19) documented an evaluation of activity limitation; however, a standard measure (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many studies omitted the information needed to assess the reliability of ascertainment of CP, including age range at diagnosis and average age at recruitment, or as pertinent to the SCPE whether the child was ‘at least 4 years old when assessed’ 13 . Ten studies (18%) erroneously stated that they were compliant with the SCPE guidelines whereas the details on age at recruitment (Table S1) indicated that they were not, in the absence of any statement regarding confirmation of the diagnosis from the age of 4 years 21–30 . A third of studies ( n =19) documented an evaluation of activity limitation; however, a standard measure (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…13 Ten studies (18%) erroneously stated that they were compliant with the SCPE guidelines whereas the details on age at recruitment (Table S1) indicated that they were not, in the absence of any statement regarding confirmation of the diagnosis from the age of 4 years. [21][22][23][24][25][26][27][28][29][30] A third of studies (n=19) documented an evaluation of activity limitation; however, a standard measure (i.e. Gross Motor Function Classification System) was undertaken in only 12 of these 19 studies (Table S3).…”
Section: Adequacy Of Reportingmentioning
confidence: 99%
“…The gene is mapped to chromosomal region 12q24. Several studies indicate that NOS1 variants are associated with such disorders as Alzheimer's disease (Mishizen-Eberz et al, 2004), schizophrenia (Shinkai et al, 2002;Saadat, 2010), and Parkinson's disease (Hancock et al, 2008;Yu et al, 2018). Using reverse-transcription polymerase chain reaction (RT-PCR), some authors (Freudenberg et al, 2015) demonstrated that protein expression of NOS1 is constitutively high in ovarian cancer cell lines and that mRNA expression of NOS1 varies among such cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…In general, CP is regarded as the result of the combined effects of multiple genes and environmental factors. Moreover, CP has been reported to have multiple susceptibility genes, including IL-6, NOS1, OLIG2, ATG5, and ATG7 (Xu et al, 2017;Yu et al, 2018;Sun et al, 2019;Xia et al, 2019).…”
Section: Introductionmentioning
confidence: 99%